(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The present study compares argumentation essays written by Non-Native Speaker (NNS) students to ones by Native Speaker (NS) students by looking at the use of causal relation and the Problem-Solution text pattern, drawing on the clause-relational approach. The study focuses on how the word problem, marking the discourse as a shell noun, is involved in these patterns. By examining the relation between problem and verb, and also interpreting a change in the Problem-Solution discourse stages, this paper will show that problem in the NS essays was mostly involved in causal relation and contributed to forming the conventional Problem-Solution pattern, while in the NNS essays, half of the instances of problem were in non-causal relation and formed random and irregular discourse patterns. This sometimes occurred with problem in causal relation, accounted for by such factors as types of verbs combined with problem, forms of the verbs, and subject types in the sentence. This paper will show some clear correlations between expressing causal relation and constructing the regular Problem-Solution pattern, and discuss pedagogical implications. The findings will be useful in the teaching of advanced level students so that they can write more effective and readable argumentation essays.